Three Preconfederation Painters of the Canadian City. Part III. Joseph Légaré - Caulfield, Jon (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1988)
James Cockburn, James Duncan and Joseph Légaré were the foremost painters of pre-Confederation Canadian cityscape and city life. Their work may be treated as cultural artifacts, linked to and suggesting insights about the period's social life; as aesthetic objects within the semi-autonomous realm of "art," to be treated within the context of critical sociology; or as historical documents offering direct evidence about pre-Confederation urban physical and social landscape. The present article emphasizes the first approach, while also indicating some directions for inquiry within the second and third approaches.